PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PEMERINTAHKABUPATEN BANDUNG - Edo Endrawan, - (2007)
The professional apparatus structuring in local autonomy management should be main priority, because reformation expecting qualified government, able to dopublic services, empowerment, andsocio economic development. Good Performance has not yet become entreched in any departments of local government, in this case Regency of Bandungs and no developed and applied competence models to measure of performance accurately to be obstacle in form ofoptimal performance. The aims of research are to finds out and discuss about organization culture and condition of employee competence in local government, organization culture effect, and employee competence. Based On Validity and reliability tests, all items is valid and reliable to managed bystatistical technique. Performance influenced by organization culture factor about 41,21%, while remain of 58,79% is other. Performance influencedby competence of 54,61 %, while remain of 45,39% is another one Large performance when there are no competence and organization culture (Xi and X2 = 0) is 6,657. It will increase about 0,175 when culture increase of 1. Performance increases for 0,412 when competences arise of 1. Organization culture and competence givea significant effecttoward performance